Platão e a terceira margem do rio: um estudo sobre divisão e ontologia das ideias no Sofista - Silva, André Luiz Braga da (2012)
In Plato\'s dialogue Sophist, the character Strange from Elea states, as main process of his philosophic activity, the Method of Division. Particularities of the process as eleatic origin, multiplicity of definitions about the same subject, and incompatibility with ideas held by character Socrate in another works lead always scholars to disagreements about the continuity and unity of platonic thought after the Sophist, especially about Theory of Forms. From the analysis of the method, as well on its form as matter, this paper wanna require for Division a possibility of joining with Plato\'s Ontology.